Liquidez internacional e crescimento econômico: uma análise Pós-Keynesiana da experiência mundial - Daniela Almeida Raposo Torres (2009)
In this research, we seek to investigate the theoretical and empirical relevance of international liquidity in establishing economic development in different countries. Particularly, we tests if international liquidity effects on investments in developed countries is different from those in developing ones, where Innovation National System (SI) is not relatively developed. The dissertation is structured in four parts, in the form of self-contained chapters, which are related among themselves. In the first chapter, we present keynesian theoretical references in order to analyze and understand the relationship between international liquidity cycles and economic growth cycles. In the following chapter, we define SI in accordance with the Evolutionary literature and show the close relationship between growth and economic development. In the third chapter, these theoretical elements are used as important reference to the contribution we are trying to offer to the theoretical and empirical debate about the difference between developed and developing countries in what growth rates are concerned. Still in the third chapter, we delineate a circular cumulative causal circuit which tends to perpetuate the context of least developed countries of the SI of developing economies. Finally, we elaborate and estimate an investment model in order to study the relationship between SI, international liquidity and economic growth. The research make a distinction between developed and developing economies and try to find an association between international liquidity and investment in countries where SI is immature. The analysis is done by an econometric estimation using the panel-corrected standard error (PCES) method, which is adequate for dealing with panel data. Finally, based on theoretical and empirical foundations, we conclude that growth cycles in developing economies where SI is not developed depend more on international liquidity cycle when compared to developed countries.